Le sette opere di Misericordia - Salvemini, Francesca (Archeomatica, 2014)
The Seven Acts of Mercy are juxtaposed in the navigation on the network and to the recovery open acces of data and events not only on the Roman scene even on the web dedicated to Caravaggio.